Nodulation of Lupinus albus by Strains of Ochrobactrum lupini sp. nov. - Trujillo, Martha E. (American Society for Microbiology, 2005)
The nodulation of legumes has for more than a century been considered an exclusive capacity of a group of microorganisms commonly known as rhizobia and belonging to the α-Proteobacteria. However, in the last 3 years four nonrhizobial species, belonging to α and β subclasses of the Proteobacteria, have been described as legume-nodulating bacteria. In the present study, two fast-growing strains, LUP21 and LUP23, were isolated from nodules of Lupinus honoratus. The phylogenetic analysis based on the 16S and 23S rRNA gene sequences showed that the isolates belong to the genus Ochrobactrum. The strains were able to reinfect Lupinus plants. A plasmid profile analysis showed the presence of three plasmids. The nodD and nifH genes were located on these plasmids, and their sequences were obtained. These sequences showed a close resemblance to the nodD and nifH genes of rhizobial species, suggesting that the nodD and nifH genes carried by strain LUP21(T) were acquired by horizontal gene transfer. A polyphasic study including phenotypic, chemotaxonomic, and molecular features of the strains isolated in this study showed that they belong to a new species of the genus Ochrobactrum for which we propose the name Ochrobactrum lupini sp. nov. Strain LUP21(T) (LMG 20667(T)) is the type strain.